2017
DOI: 10.1016/j.str.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Heterotrimeric Integrin-Binding Region of Laminin-111

Abstract: SummaryLaminins are cell-adhesive glycoproteins that are essential for basement membrane assembly and function. Integrins are important laminin receptors, but their binding site on the heterotrimeric laminins is poorly defined structurally. We report the crystal structure at 2.13 Å resolution of a minimal integrin-binding fragment of mouse laminin-111, consisting of ∼50 residues of α1β1γ1 coiled coil and the first three laminin G-like (LG) domains of the α1 chain. The LG domains adopt a triangular arrangement,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…Mapping of the detected modifications onto a complete 3D structure cannot be accomplished at present, as only a small number of partial structures are available. A recently structure (PDB entry: 5MC9) [83] contains the coordinates of the xLG1-3 domains, as well as~50 residues of the coiled coil (α1β1γ1). These sequences contain 20 Tyr, of which 11 were identified as chlorination targets, 14 Met, of which 7 were detected as sulfoxides, and 4 Trp, with 3 of these detected as oxidised species (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mapping of the detected modifications onto a complete 3D structure cannot be accomplished at present, as only a small number of partial structures are available. A recently structure (PDB entry: 5MC9) [83] contains the coordinates of the xLG1-3 domains, as well as~50 residues of the coiled coil (α1β1γ1). These sequences contain 20 Tyr, of which 11 were identified as chlorination targets, 14 Met, of which 7 were detected as sulfoxides, and 4 Trp, with 3 of these detected as oxidised species (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of modifications to (surface-exposed) Tyr 2415 is of particular interest as it is situated close to Glu 1605 (indicated in brown, in Fig. 11, panel A), which is essential for interactions with integrins [83][84][85]. Modification of this residue, and possibly others nearby, may therefore affect integrin binding to laminins, and hence cell binding to the ECM [4,85].…”
Section: Discussionmentioning
confidence: 99%
“…Pulido et al . ( 13 ) noted that the LG1 and LG2 surfaces on either side of the γ1-tail are more highly conserved than that of LG3, implying that the residues involved in integrin binding lie within the highly conserved surfaces. Our exhaustive disulfide cross-link screening with Cys-substituted LM511E8 and α6β1 integrin showed that the γ1-tail came into close contact with and cross-linked with integrin β1 residue 133 near the β1-MIDAS even in the absence of γ1E1607.…”
Section: Discussionmentioning
confidence: 99%
“…DNA coding for residues 232-959 of human XT1 was amplified from a cDNA clone (Dharmacon) using Q5 polymerase (New England Biolabs) and ligated into a modified pCEP-Pu vector that adds a TEV protease-cleavable His-tag at the N-terminus of the secreted protein ( Pulido et al., 2017 ). The vector was transfected into FreeStyle 293-F cells (Thermo Fisher Scientific) using linear polyethylimine (MW 25,000; Polysciences).…”
Section: Methodsmentioning
confidence: 99%